4-Methylmorpholinium bromide - Ji-Yuan Yao (Acta Crystallographica Section E, 2010)
The six-membered ring in the title salt, C5H12NO+·Br−, has a chair conformation. In the crystal, the cations are linked to the anions by N—H...Br hydrogen bonds.